2007
DOI: 10.1017/s1092852900021386
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Syndrome in Elderly Patients Treated for Psychotic Depression with Atypical Antipsychotics and Antidepressants: Two Case Reports

Abstract: We report two cases of serotonin syndrome in elderly patients during treatment of psychotic depression with atypical antipsychotics and antidepressants. The first case is a 69-year-old man who was admitted for depression with psychosis and treated with trazodone, risperidone, and sertraline. Subsequently, he developed myoclonus, tremor, cogwheel rigidity, and diaphoresis. The second case is a 72-year-old female initially admitted to a medical inpatient unit for a change in mental status that presented as incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…All cases had exposure to at least one serotonergic agent. Atypical antipsychotics such as quetiapine and ziprasidone have demonstrated partial agonism at 5‐HT1A receptors and have been implicated in case reports as causative agents in addition to SSRIs in serotonin syndrome . However, it is important to note that although many cases involved atypical antipsychotics, these substances are more likely to cause neuroleptic malignant syndrome rather than serotonin syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cases had exposure to at least one serotonergic agent. Atypical antipsychotics such as quetiapine and ziprasidone have demonstrated partial agonism at 5‐HT1A receptors and have been implicated in case reports as causative agents in addition to SSRIs in serotonin syndrome . However, it is important to note that although many cases involved atypical antipsychotics, these substances are more likely to cause neuroleptic malignant syndrome rather than serotonin syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Atypical antipsychotics such as quetiapine and ziprasidone have demonstrated partial agonism at 5-HT1A receptors and have been implicated in case reports as causative agents in addition to SSRIs in serotonin syndrome. [10][11][12][13][14][15] However, it is important to note that although many cases involved atypical antipsychotics, these substances are more likely to cause neuroleptic malignant syndrome rather than serotonin syndrome. In cases in which atypical antipsychotics were ingested, another serotonergic agent commonly associated with serotonin syndrome was also ingested.…”
Section: Re Sultsmentioning
confidence: 99%
“…These interactions could lead to increased concentrations of various drugs or serotonin levels, which could be associated with serotonin syndrome. Finally, FAERS and literature case analyses demonstrated that second‐generation antipsychotics alone can be associated with serotonin syndrome, but in most reported cases serotonin syndrome occurs when second‐generation antipsychotics are given with other serotonergic agents …”
Section: Discussionmentioning
confidence: 99%
“…Although depicted separately in this figure, it should be supposed as a continuum without definite gaps between the groups. been several case reports where the diagnosis of serotonin toxicity or serotonin syndrome is given to the clinical symptoms subsequent to the treatment with atypical antipsychotics, e.g., risperidone [122][123][124], olanzapine [125][126][127][128], quetiapine [124,129], ziprasidone [130], and perospirone [131], prescribed in combination with other psychotropic drugs with serotomimetic properties, mostly SSRIs. In these case reports, the putative mechanisms underlying the development of serotonin syndrome associated with atypical antipsychotics are supposed to be ascribed to their potent 5-HT 2A receptor antagonism or to their pharmacokinetic interaction with coincidently prescribed SSRIs through the common cytochrome P450 isoenzyme metabolism.…”
Section: Discussionmentioning
confidence: 99%